1965
DOI: 10.1111/j.2153-3490.1965.tb00193.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Boussinesq approximation and its role in the theory of internal waves

Abstract: Most studies of the dynamics of fluids with weak density gradients use the Boussinesq approximation, which neglects density variations in the inertial terms of the equation of motion. The significance of this approximation is investigated here. As a general matter, it appears that care is called for in the use of the approximation if quantities other than the non-dimensional density difference are small. Also, the existence of certain phenomena of interest and importance may depend on the small terms neglected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 5 publications
2
44
0
Order By: Relevance
“…The traditional justification for setting e = 0 may be stated in our notation as the fact that h 2 a «7T"2 for most stratifications of real interest. This widely used approximation has the advantage that it simplifies the analysis considerably; for instance, it makes the transformation ( However, some researchers [4,24] have concluded that the Boussinesq approximation can be delicate and can lead to significant inaccuracy when finite-amplitude solutions, especially solitary waves, are considered. Therefore, we shall proceed with our analysis and computation without this simplification, recognizing that the Boussinesq case may be included in our exact formulation merely by setting e = O.…”
Section: Semilinear Form Of Eigenvalue Problemmentioning
confidence: 99%
“…The traditional justification for setting e = 0 may be stated in our notation as the fact that h 2 a «7T"2 for most stratifications of real interest. This widely used approximation has the advantage that it simplifies the analysis considerably; for instance, it makes the transformation ( However, some researchers [4,24] have concluded that the Boussinesq approximation can be delicate and can lead to significant inaccuracy when finite-amplitude solutions, especially solitary waves, are considered. Therefore, we shall proceed with our analysis and computation without this simplification, recognizing that the Boussinesq case may be included in our exact formulation merely by setting e = O.…”
Section: Semilinear Form Of Eigenvalue Problemmentioning
confidence: 99%
“…In the case of a homogeneous fluid, Eqs. (7) and (9) Finally, another phenomenon of stratified fluids (Long, 1965) that has application to the rotating homogeneous case is the solitary wave at rest in a basic flow wo{x o )' In the present case there is no wave when W o is constant because the governing equation (15)…”
Section: Homogeneous Liquidmentioning
confidence: 99%
“…The KdV model has been suggested for the studying of nonlinear internal waves in the mid 1960's, in a stationary variant of the KdV equation (Long, 1965;Benjamin, 1966). Between 1970 and, this model was developed and was adjusted to explain various atmospheric and ocean processes.…”
Section: Analytical Model Of Nonlinear Internal Gravity Wavesmentioning
confidence: 99%
“…Nevertheless, some mathematical research reveals that the passage from a full hydrodynamic model to the limit of a quasistatic model is absent (Long, 1965;Kshevetskii andLeble, 1985, 1988). The reason for this strange phenomenon is concealed in equation nonlinearity.…”
Section: Introductionmentioning
confidence: 99%